TEPATAN DAN KESESUAIAN ANALISIS KE PENULISAN KODE DIAGNOSIS DAN TINDAKAN KASUS OBSTETRI PASIEN SJSN DI RSUP DR.SARDJITO YOGYAKARTA - , ELVIRA KUSUMASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Coding is very important in financial terms even more so for the social security payment systems that use claims. Errors in coding can lead to financial losses for hospitals. On January 1, 2014, Indonesia began to implement a new health social insurance system which is managed by BPJS (Social Security Agency Business). RSUP Dr. Sardjito, Yogyakarta is one of the bigest referral hostpital that cause many guaranteeâs patient. The accurancy and suitability diagnostic and procedure code very important to specify how much financial terms and to take any decision for hospital manajement. In RSUP Dr. Sardjito, Yogyakarta one of the manies case that claim give back to hospital is obstetryâs case. Objective: To know about the implementation of charging, percentage accurancy of code, suitability percentage of code in the medical record file and sheet claims and medical record staffs attempt to accurancy filling diagnosis and procedure codes of obstetric patients SJSN action cases in RSUP Dr. Sardjito, Yogyakarta. Methods: This type of research was a descriptive study used a qualitative approach and the case study design. The objek was medical record file and sheet claims in Januari 2014. The subjek was three people who coding hospitalization of guaranteeâs patient and one head of guarantee instalation as triangulation The technique of collecting data used interviews, observation and documentation studies. Results: Implementation of coding diagnoses and acts on exit and entry summary sheet INA-CBG's claim inpatients 9 officers conducted by coding. Encoding patient diagnosis based on ICD-10 version of 2005 and actions based on ICD-9-CM 2007 version . The coding diagnoses and inpatient action at INA CBG's claim sheet together with the implementation of diagnosis coding and entry summary action on exit. Percentage accuracy of diagnosis codes in the summary entry exit criteria are as much as 72.77% A